The Prevailing Issues Pertaining to Students’ Conception About Accountancy - Roy, Sandhiya (American Journal of Education and Learning, 2019)
The initial exposure to accounting studies sets the foundation of whether students would want to pursue a career path in accounting. The introductory accounting course is crucial because this creates an overall impression of the work of accountants. This study aims to discover the development in the perception of undergraduate students about accounting over two decades. Further to this, the study seeks to identify the issues related to perceptions in Fiji and whether these findings are similar to those carried out by international studies? To address these research questions, this study employs both empirical and non-empirical approach to data collection. A systematic literature review of the student perceptions from the period of 1995 – 2015 is carried out. In addition, a survey is carried out to examine the perceptions of undergraduate accounting major students, in their first core course, at one of the three universities in Fiji in the year 2017. The responses from forty-five Introductory Financial Accounting students from this university reveal that more than fifty percent are having a positive attitude towards accountancy profession however they find accounting a difficult subject of study and accountants having poor work-life balance. This study makes a number of recommendations to address the two key issues that have been prevailing over the years: accounting subject difficulty and work-life balance issue of accountants.